Rozwiąż równania:
z1
a)3(x-4)-4(2x-7)=2(x+5)
b)2(2x-3)+3(4-x)=-(x+1)
c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
z2
a)2(x-7)-3(x+2)=4(x+3)+2(x-9)
b)-3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
c)-8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
d)6(4-x)+5(2x-5)=4(x-1)-3(4-x)
z3
a)3(3-x)+2x=8-2(x-1)
b)4x+5-(3x+6)=2(2+x)-4
c)4-5(3-x)=-x-(3-2x)
d)x-(7+2x)=2(x-1)+1

Proszę o całe rozwiązania, a nie same wyniki!

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-01T18:27:31+01:00
Z1
a)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
-5x+16=2x+10
-5x-2x=10-16
-7x=-6 /(-7)
x=- 6/7
b)2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
x+6=-x-1
x+x=-1-6
2x=-7 /2
x=-3,5
c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
-2x-6=7x-8
-2x-7x=-8+6
-9x=-2 /-9
x=2/9
d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
3x+12=5x-6
3x-5x=-6-12
-2x=-18 /-2
x=9
z2
a)2(x-7)-3(x+2)=4(x+3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
-x-20=6x-6
-x-6x=-6+20
-7x=14 /-7
x=-2
b)-3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x-18-12x-48=-8-2x+9x+72
-15x-64=7x+64
-15x-7x=64+64
-22x=128 /-22
x=-5 8/22
c)-8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x-6+8x-4
-5x-1=4x-2
-5x-4x=-2+1
-9x=-1 /-9
x=1/9
d)6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
4x-1=7x-16
4x-7x=-16+1
-3x=-15 /-3
x=5
z3
a)3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
9-x=10-2x
-x+2x=10-9
x=1
b)4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
x-1=2x
x-2x=1
-x=1
x=-1
c)4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
-11+5x=x-3
5x-x=-3+11
4x=8 /4
x=2
d)x-(7+2x)=2(x-1)+1
x-7-2x=2x+2+1
-x-7=2x+3
-x-2x=3+7
-3x=10 /-3
x=- 10/3 = 3 2/3


2010-03-01T18:33:14+01:00

z1
a)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x=10+12-18
-7x= 4
x= - 4/7

b)2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x= -x-1
4x-3x+x= -1+6-12
x= -7

c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-3x= -3 +6 + 4x -2
2x-3x-4x = -3-2 +6 +6+12
-5x= 19
x= - 3 i 4 /5

d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x= 4x-2-4+x
6x-3x-4x-x = -2-4-6-6
-2x = -18
x =9


z2
a)2(x-7)-3(x+2)=4(x+3)+2(x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x = 12-18+14+6
-7x= 14
x = -2

c)-8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
d)6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12-3x
-6x+10x-4x+3x = -4-12-24+25
3x= -15
x= -5

z3
a)3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x-2
-3x+2x+2x= 8-2-9
x= -3


b)4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4x+2x-4
4x-3x-2x-4x=-4-5+6
-5x= -3
x= 3/5


c)4-5(3-x)=-x-(3-2x)
4-15-5x= -x-3+2x
-5x+x-2x = -3 -4+15
-6x = 8
x = - 1 i 2 /6

d)x-(7+2x)=2(x-1)+1
x-7-2x=2x-1+1
x-2x-2x= -1+1+7
-3x= -7
x= 2 i 1/7
2010-03-01T18:37:08+01:00
Z1
a)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28 = 2x+10
-5x+14 = 2x+10 /+5x -10
7x = 24
x = 3 i 3/7

b)2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x = -x-1
x+6 = -x-1 /+x -6
2x = -7 /:2
x = -7/2 czyli -3,5


c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x = -3x-6+4x-2
-2x-18 = x-8 /+2x +8
3x = -10 /:3
x = -10/3
x = -3 i 1/3


d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x = 4x-2-4+x
3x+12 = 5x-6 /-3x +6
2x = 18 /:2
x = 9


z2
a)2(x-7)-3(x+2)=4(x+3)+2(x-9)
2x-14-3x-6 = 4x+12+2x-18
-x-20 = 6x-6 /+x +6
7x = -14 /:7
x = -2


b)-3(x+6)-6(2x+8)=-2(4-x)+9(x+8)
-3x-18-12x-48 = -8+2x+9x+72
-15x-66 = 11x+64 /+15x -64
26x = -130 /:26
x = -5



c)-8(x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15 = -4x-6+8x-4
-5x-1 = 4x-10 /+5x +10
9x = 9 /:9
x = 1


d)6(4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25 = 4x-4-12+3x
4x-1 = 7x-16 /-4x +16
3x = 15 /:3
x = 5

z3
a)3(3-x)+2x=8-2(x-1)
9-3x+2x = 8-2x+2
9-x = -2x+10 /+2x -9
x = 1


b)4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6 = 4+2x-4
x-1 = 2x /-x
x = -1


c)4-5(3-x)=-x-(3-2x)
4-15+5x = -x-3+2x
5x-11 = x-3 /-x +11
4x = 8 /:2
x=2


d)x-(7+2x)=2(x-1)+1
x-7-2x = 2x-2+1
-x-7 = 2x-1 /+x +1
3x = -6 /:3
x = -2